Confirmatory Factor Analysis of the Mackey Childbirth Satisfaction Rating Scale in Brazil - Lopes, Fernanda; Nakamura, Mary Uchiyama; Araujo Júnior, Edward; Nomura, Roseli Mieko Yamamoto (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
To examine the psychometric properties of the Mackey Childbirth Satisfaction Rating Scale (MCSRS), previously translated and adapted to Brazilian Portuguese. A methodological and cross-sectional study with data collected at a low-risk maternity hospital, period of 2017 and 2018. The inclusion criteria were early postpartum, maternal age between 18 and 34 years, birth of a live infant, and birth over 36 weeks’ gestation. The Brazilian Portuguese version of the MCSRS with 34 items in six subscales (self, partner, baby, nurse, physicians, and overall childbirth satisfaction) was administered in a face-to-face interview. Psychometric analyses assessed internal consistency using Cronbach’s alpha and McDonald’s omega, and confirmatory factor analysis (CFA) examined dimensionality. The population included 411 participants. Confirmatory factor analysis (CFA) indicated a good fitness for the model, comparative fit index (CFI) and goodness-of-fit index (GFI)=0.99; root mean square error of approximation (RMSEA) (0.07; 95% CI 0.07–0.08); incremental fit index (IFI) and Tucker–Lewis index (TLI)=0.99, which confirmed the six subscales identified in the original scale. The factorial loads of the items were all above 0.70. For the questionnaire’s overall reliability, Cronbach’s alpha was 0.96 and McDonald’s omega was 0.97. The MCSRS is a valid instrument, being that all subscales had good reliability indexes. CFA inclusion criteria also encompassed women who underwent an unplanned cesarean section, thus extending the use of the MCSRS.
Keywords: Childbirth satisfaction; labor; psychometric; questionnaire; validation studies